2012
DOI: 10.1002/rcm.5329
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tiagabine degradation products using liquid chromatography with electrospray ionization multistage mass spectrometry and ultra‐performance liquid chromatography/high‐resolution mass spectrometry

Abstract: Nine degradation products of TGB were identified. Some diagnostic MS/MS product ions, characteristic of the piperidine or thiophene moiety, were highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Rustum et al 11 proposed a chiral HPLC method to quantify the S-(+)-enantiomer of TBN in its bulk drug and to separate its S (+), R (−)-enantiomers as well as two chiral precursors. Hubert-Roux et al 12 identified degradation products of TBN using LC-MS-MS and UPLC-HRMS. Rajasingam et al 13 studied the stress degradation and proposed an RP-HPLC method to determine TBN in presence of its degradation products.…”
Section: Introductionmentioning
confidence: 99%
“…Rustum et al 11 proposed a chiral HPLC method to quantify the S-(+)-enantiomer of TBN in its bulk drug and to separate its S (+), R (−)-enantiomers as well as two chiral precursors. Hubert-Roux et al 12 identified degradation products of TBN using LC-MS-MS and UPLC-HRMS. Rajasingam et al 13 studied the stress degradation and proposed an RP-HPLC method to determine TBN in presence of its degradation products.…”
Section: Introductionmentioning
confidence: 99%